Electrochemically controlled detection of adrenaline on poly(2‐aminobenzylamine) thin films by surface plasmon resonance spectroscopy and quartz crystal microbalance. (18th October 2013) - Chuekachang, Sopis; Janmanee, Rapiphun; Baba, Akira; Phanichphant, Sukon; Sriwichai, Saengrawee; Shinbo, Kazunari; Kato, Keizo; Kaneko, Futao; Fukuda, Nobuko; Ushijima, Hirobumi
Abstract : In this study, we present an electrochemically controlled surface plasmon resonance (EC‐SPR) biosensor to detect adrenaline on poly(2‐aminobenzylamine) (P2ABA) thin films. The P2ABA thin films are stable and display electroactivity in a neutral PBS solution. Specific detection of adrenaline was performed on P2ABA thin films because the benzylamine groups in the P2ABA structure could specifically react with adrenalines. Adrenaline was detected in real time by EC‐SPR spectroscopy, which provides an EC‐SPR reflectivity change on the P2ABA thin film upon adrenaline injection. The measured responses were quite different from those for uric acid and ascorbic acid, which are major interferences in adrenaline detection. The electrochemically applied potential facilitates the specific detection of adrenaline. In addition, the detection of adrenaline on the P2ABA thin films was investigated by a quartz crystal microbalance technique. The detection limit for adrenaline at open circuit potential was 10 pM. The present study provides a useful information on the detection of adrenaline on the P2ABA thin films. Copyright © 2013 John Wiley & Sons, Ltd.